Response of HTS tapes to a parallel ac magnetic field in the vicinity of the superconducting transition - Fisher, L.M.; Voloshin, I.F.; Yampol’skii, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We have studied the temperature dependence of the ac magnetic susceptibility χ(T) = χ′(T) + iχ″(T) of YBCO tapes in a parallel magnetic field in both the Meissner and vortex states. For the vortex state, we have observed two maximums in the χ″(T) dependence. The position and the magnitude of one of these maxima are described well by the nonlocal critical state model. The second maximum and corresponding kink in the function χ′(T) observed close to the temperature Tc of the superconducting transition are unexpected. The origin of this maximum cannot be explained within the usual notions of the high-temperature superconductivity. We suppose that it is related to some magnetic restructuring in the superconducting layer just above Tc. Our results put a question on the correctness of the interpretation of some previous microwave experiments.